529 Cancer cells educate natural killer cells to a metastasis promoting cell state. (9th November 2020) - Chan, Isaac; Knútsdóttir, Hildur; Ramakrishnan, Gayathri; Padmanaban, Veena; Warrier, Manisha; Ramirez, Juan Carlos; Bader, Joel; Jaffee, Elizabeth; Ewald, Andrew
Abstract : Background: Metastatic disease drives breast cancer mortality. We recently discovered that leading cells at the invasive edge of mammary tumor organoids retain a conserved basal epithelial program defined by their expression of keratin-14 (K14), establishing K14 as a good marker of invasive breast cancer cells. K14-positive invasive cells also exhibit characteristics that make them targets of immunosurveillance by natural killer (NK) cells. While NK cells are key immune mediators in the control of metastasis, our understanding of the specific mechanisms behind this regulation and its eventual evasion by metastatic cells remains incomplete. Methods: We have developed a novel preclinical 3D co-culture assay to discover mechanisms behind interactions between K14+ invasive breast cancer cells and NK cells. Combined with in vivo assays of metastasis, we are able to determine how NK cells limit the early stages of metastasis and also how tumor cells can influence key NK cell properties. Results: In ex vivo co-culture assays of NK cells isolated from healthy mouse donors and mammary tumor organoids from MMTV-PyMT and C31T mouse models of breast cancer, we demonstrate that NK cells limit the early stages of metastasis. Antibodies to invasive K14+ cells were able to enhance the ability of NK cells to limit colony formation, suggesting antibody-dependent cell mediated cytotoxicity. Surprisingly, when isolated from tumor bearing mice, NK cells did not limit invasion and instead promoted colony formation. The in vivo adoptive transfer of NK cells from healthy donors prevents the progression of early lung metastatic seeds to macrometastases, while the adoptive transfer of cells isolated from tumor bearing donors promotes macrometastatic development. Transcriptomic analysis of reprogrammed NK cells demonstrate they have similar profiles to resting NK cells. This growth promoting phenotype can be reversed with antibodies targeting inhibitory cell surface receptors or the epigenome. Conclusions: Our ex vivo and in vivo data demonstrate that healthy donor NK cells can limit metastasis through the directed cytotoxicity against pioneering K14+ invasive cells. However, prolonged exposure to tumors reprogram NK cells from tumor killing to tumor promoting, specifically in promoting the outgrowth of macrometastases. Further, we can neutralize this effect using NK cell specific inhibitory antibodies and epigenetic modifiers. This is the first time inhibitory signaling on NK cells have been linked with a growth promoting phenotype. These data can provide insight into when the use of NK cell directed therapies can be used to treat or prevent clinically relevant metastatic disease.